Penguatan Keterampilan Berkomunikasi Efektif melalui Strategi Interaksi Edukatif antara Guru dan Anak Usia Dini - Nadia Nur Amalia Adawiyah; Annisa Fahmi Mannassai; Alisya Sarah Fitriyani; Dwi Cahyani L; Debriyanti Mahmud (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Communication skills are a fundamental foundation in early childhood development. Teachers, as the main figures in the learning process, play a strategic role in creating educational interactions that support the development of children's communication abilities. This study aims to describe educational interaction strategies that can strengthen effective communication among early childhood learners. Using a qualitative-descriptive approach, data were obtained from observations, teacher interviews, and literature studies. The results show that strategies such as responsive communication, role play, interactive storytelling, and proper language modeling can enhance children's confidence in communication. This study recommends continuous training for early childhood educators in implementing adaptive and contextual communication strategies.